Soil Reserves of Potassium: Release and Availability to Lolium perenne in Relation to Clay Minerals in Six Cropland Soils from Eastern China. (7th June 2017) - Li, Ting; Wang, Huoyan; Chen, Xiaoqin; Zhou, Jianmin
Abstract: An 8‐month greenhouse experiment with ryegrass ( Lolium perenne L.) examined the relationship between the dynamics of potassium (K) reserves in soil and changes in clay minerals, using X‐ray diffraction. The capacity of soil to release K was consistent with its ability to supply it and was the highest in the soil samples collected from Laiyang (H1 T2 a), Harbin (H1 T1 ) and Beibei (H2 T4 ), followed by the sample from Jiangyan (H1 T2 b), and the lowest in the samples from Gao'an (H2 T3 a) and Wangcheng (H2 T3 b). Removal of soil K decreases the intensity of reflections for illite and increases that for interstratified clay minerals. The centre of gravity values of the clay fractions was significantly negatively correlated to the depletion of soil K reserves, as ascertained through chemical extraction or through plant action. The quantitative regression equations between the centre of gravity values and the dynamics of soil reserves of K can be used for predicting the release and plant availability of K even without growing a crop. Copyright © 2017 John Wiley & Sons, Ltd.